The letters of Paul : conversations in context - Roetzel, Calvin J. (Louisville, Kentucky.: : WJK, 2015)
"This is the sixth edition of the classic textbook that has been introducing Paul and his writing to seminary and undergraduate students for over forty years. Roetzel provides a comprehensive look at Paul in light of recent scholarship and theological understandings of Paul. This new edition includes four brand-new sections on the following: the chronology of Paul's letters; Paul's concept of "law" in the context of messianic expectation; the religious and political contexts in which Paul's letters were written; and Jewish understandings of Gentiles and Paul's mission to include them among the elect of God. This long-established textbook is the ideal choice for any student of Paul"--
Includes bibliographical references and index.
Keywords: Bible. -- Textbooks; RELIGION / Biblical Studies / Paul's Letters; RELIGION / Biblical Studies / History & Culture; RELIGION / Biblical Studies / Bible Study Guides